Hybrids of cationic [4]helicene and N-heterocyclic carbene as ligands for complexes exhibiting (chir)optical properties in the far red spectral window. Issue 31 (19th March 2021) - Tarrieu, Robert; Delgado, Irene Hernandez; Zinna, Francesco; Dorcet, Vincent; Colombel-Rouen, Sophie; Crévisy, Christophe; Baslé, Olivier; Bosson, Johann; Lacour, Jérôme
Abstract : A cationic Helicene-NHC hybrid is readily prepared and used for the construction of Rh I, Au I and Au III complexes. Ligand controlled chiroptical properties in the far-red spectral window are observed. Abstract : Synthesis, electronic and structural properties of a chiral NHC bearing a N-bonded cationic [4]helicene moiety are reported. This ligand is used to construct Au I, Au III and Rh I complexes exhibiting far-red (chir)optical properties regardless of the metal.